A MULTIMODAL STYLISTIC ANALYSIS OF SELECTED ENDSARS PROTEST PLACARDS ON SOCIAL MEDIA - Omolabi , Ibrahim (University of Chitral Journal of Linguistics and Literature, 2026)
Several studies have been done on the EndSARS protest in Nigeria using different linguistic approaches to analyse and interpret data. However, little attention has been given to the combination of stylistic and multimodal approaches to the study of placards to unravel how textual resources contribute to the style of meaning in texts.  The paper therefore examines the meaning and style of semiotic resources in the selected data. Five (5) purposively selected placards from the EndSARS protest were analysed, using Kress and van Leeuwen's (2006) social semiotic theory and foregrounding theory as the theoretical framework. It was discovered that placards on EndSARS protests are presented with a combination of several modes, such as text, colour, and images. These modes serve the purpose of creating meaning effectively, and this can be proved in the display of placards selected for analysis. The study concludes that placards have different messages which can be decoded through multimodal and stylistic approaches.